2021
DOI: 10.1371/journal.pone.0255124
|View full text |Cite
|
Sign up to set email alerts
|

Assessing national cervical cancer screening guidelines: Results from an HIV testing clinic also screening for cervical cancer and HPV in Soweto, South Africa

Abstract: Objective A screening centre in Soweto, South Africa (SA), investigated high-risk human papillomavirus (HR-HPV), HIV, cervical cancer risk amongst women. Methods This cross-sectional study (June 2018-March 2019) describes screening results (Roche Linear Array HPV test and Pap smear liquid based cytology) and history of screening (known HIV status, antiretroviral therapy [ART] use, previous Pap smears). Data were stratified by age group (18–29, 30+ years), HIV status, Pap smear results and tested for statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Watson-Jones et al (73) previously assessed the feasibility and acceptability of delivering other adolescent health services alongside HPV vaccination in Tanzania and found general support for the intervention among key stakeholders. Similar findings have been reported in the South African context (63). What concerns stakeholders about these integrated approaches aside from the increased workload is the limited availability of infrastructure such as transportation for vaccinators, and the fact that frequent deployment of vaccinators to schools to deliver additional services could have a negative impact on routine health facility visits.…”
Section: Opportunities For Delivering Other Adolescent Health Services Alongside the Hpv Vaccinesupporting
confidence: 76%
See 1 more Smart Citation
“…Watson-Jones et al (73) previously assessed the feasibility and acceptability of delivering other adolescent health services alongside HPV vaccination in Tanzania and found general support for the intervention among key stakeholders. Similar findings have been reported in the South African context (63). What concerns stakeholders about these integrated approaches aside from the increased workload is the limited availability of infrastructure such as transportation for vaccinators, and the fact that frequent deployment of vaccinators to schools to deliver additional services could have a negative impact on routine health facility visits.…”
Section: Opportunities For Delivering Other Adolescent Health Services Alongside the Hpv Vaccinesupporting
confidence: 76%
“…For AGYW between the ages of 15-25 years, the current national policy (12) does not make provision for free cervical cancer screening unless at high risk due to HIV infection or immunosuppression caused by other diseases or treatments, in accordance with global recommendations (10). Unfortunately, uptake of these screening services among HIV infected AGYW in South Africa is reported to be poor, leaving them at high risk of developing invasive cervical cancer (63). This provides further cause for extending the lifesaving benefits of the HPV vaccine to AGYW 15-25 years of age regardless of HIV status, although the feasibility of such an intervention will have to be fully researched.…”
Section: High Incidence Of Hiv Infection Among Adolescent Girls In South Africamentioning
confidence: 99%
“…Also, since the incidence of cervical cancer increases with age, older women are more likely to find screening beneficial and applicable to their health needs. However, to improve coverage, younger women especially PLOS GLOBAL PUBLIC HEALTH those at significant risk but who may be <30-years-old and HIV-negative also, need to be targeted for screening, especially that a high prevalence of HIV and high-risk HPV infections have been reported in this population in South Africa [42].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the targeted interventions to increase the uptake of cervical cancer screening in this group would be motivation and capability of the participants through environmental influence like mass media and social support. Despite having national treatment guidelines stating that every HIV women should have a Pap smear at initiation of treatment, less than half (46%) of HIV positive women screened for cervical cancer [38,[40][41][42]. However, this contradicts Ugandan study, which reported cervical cancer screening of 10% among HIV positive women [24], This suggests that integration may not suffice on its own but should be part of a multi-faceted strategy that incorporates activities that provide opportunities for serial health education (to increase awareness of risks and the need to engage the screening services), personalize risks during the clinical encounter (to motivate non-deciders to take a decision), explore and support self-efficacy (to increase the chances of women acting on their decision to test.t) and increase access (to optimize screening uptake when a woman has decided to test).…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…For women living with HIV, the South African policy on cervical cancer recommends screening be done at three-year intervals starting as soon as HIV is diagnosed [ 6 ]. South African data showed that women living with HIV had a higher prevalence of HPV infection than women who were HIV-negative because of sexual behavior and immune suppression due to HIV infection [ 7 , 8 ]. Evidence reveals that the incidence and progression of the squamous intraepithelial lesion (SIL) and cervical cancer could be reduced by early ART initiation and adherence [ 9 - 13 ].…”
Section: Introductionmentioning
confidence: 99%